Bibliometric analysis of the Journal of Civil Engineering and Management between 2008 and 2018 - Yu, Dejian; Xu, Zeshui; Antuchevičienė, Jurgita (Journal of Civil Engineering and Management, 2019)
The Journal of Civil Engineering and Management (JCEM) is a prestigious international journal in the field of engineering. This paper uses the method of bibliometric to study the status and development trends of the journal. Information was collected from the Science Citation Index (SCI) database. Firstly, the general citation structure and basic characteristics of the JCEM journal are investigated. Then, the most influential institutions, countries as well as their networks of cooperation are identified. Finally, the main research topics of the JCEM journal are explored by using the frequently used keywords. This paper explores the internal structure and development trend of the JCEM journal, which not only provides an important reference for the future development of this journal, but also provides an effective analysis method for the future evaluation of journals.